Global burden of atherosclerotic cardiovascular disease in people with hepatitis C virus infection: a systematic review, meta-analysis, and modelling study. (October 2019) - Lee, Kuan Ken; Stelzle, Dominik; Bing, Rong; Anwar, Mohamed; Strachan, Fiona; Bashir, Sophia; Newby, David E; Shah, Jasmit S; Chung, Michael H; Bloomfield, Gerald S; Longenecker, Chris T; Bagchi, Shashwatee; et al.
Summary: Background: More than 70 million people worldwide are estimated to have hepatitis C virus (HCV) infection. Emerging evidence indicates an association between HCV and atherosclerotic cardiovascular disease. We aimed to determine the association between HCV and cardiovascular disease, and estimate the national, regional, and global burden of cardiovascular disease attributable to HCV. Methods: For this systematic review and meta-analysis, we searched MEDLINE, Embase, Ovid Global Health, and Web of Science databases from inception to May 9, 2018, without language restrictions, for longitudinal studies that evaluated the risk ratio (RR) of cardiovascular disease in people with HCV compared with those without HCV. Two investigators independently reviewed and extracted data from published reports. The main outcome was cardiovascular disease, defined as hospital admission with, or mortality from, acute myocardial infarction or stroke. We calculated the pooled RR of cardiovascular disease associated with HCV using a random-effects model. Additionally, we calculated the population attributable fraction and disability-adjusted life-years (DALYs) from HCV-associated cardiovascular disease at the national, regional, and global level. We also used age-stratified and sex-stratified HCV prevalence estimates and cardiovascular DALYs for 100 countries to estimate country-level burden associated with HCV. This study is registered with PROSPERO, number CRD42018091857. Findings: Our search identified 16 639 records, of which 36 studies were included for analysis, including 341 739 people with HCV. The pooled RR for cardiovascular disease was 1·28 (95% CI 1·18–1·39). Globally, 1·5 million (95% CI 0·9–2·1) DALYs per year were lost due to HCV-associated cardiovascular disease. Low-income and middle-income countries had the highest disease burden with south Asian, eastern European, north African, and Middle Eastern regions accounting for two-thirds of all HCV-associated cardiovascular DALYs. Interpretation: HCV infection is associated with an increased risk of cardiovascular disease. The global burden of cardiovascular disease associated with HCV infection was responsible for 1·5 million DALYs, with the highest burden in low-income and middle-income countries. Funding: British Heart Foundation and Wellcome Trust.